Recurrent abscess after primary successful endo-sponge treatment of anastomotic leakage following rectal surgery - Riss, Stefan (Baishideng Publishing Group Co., Limited, 2010)
AIM: To assess long-term efficacy of initially successful endo-sponge assisted therapy. METHODS: Between 2006 and 2009, consecutive patients who had undergone primary successful endo-sponge treatment of anastomotic leakage following rectal cancer surgery were enrolled in the study. Patients were recruited from 6 surgical departments in Vienna. Clinical and oncologic outcomes were assessed through routine endoscopic and radiologic follow-up examination. RESULTS: Twenty patients (7 female, 13 male) were included. The indications for endo-sponge treatment were anastomotic leakage (n = 17) and insufficiency of a rectal stump after Hartmann’s procedure (n = 3). All patients were primarily operated for rectal cancer. The overall mortality rate was 25%. The median follow-up duration was 17 mo (range 1.5-29.8 mo). Five patients (25%) developed a recurrent abscess. Median time between last day of endo-sponge therapy and occurrence of recurrent abscess was 255 d (range 21-733 d). One of these patients was treated by computed tomography-guided drainage and in 3 patients Hartmann’s procedure had to be performed. Two patients (10%) developed a local tumor recurrence and subsequently died. CONCLUSION: Despite successful primary outcome, patients who receive endo-sponge therapy should be closely monitored in the first 2 years, since recurrence might occur.